Improving Learning Experience Through Augmented Reality Media Workshop Oriented on Local Wisdom at the Megalithic Site of Poso - Nadjamuddin, Lukman; Jamaludin, Jamaludin; Rore, Idrus; Zaky, Muhammad; Tadeko, Nurgan (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research addresses significant challenges in enhancing the quality and relevance of education in remote areas of Indonesia, particularly in Poso Regency, Central Sulawesi. The primary issues identified include low student engagement in learning activities related to local culture and history, as well as a lack of innovative teaching methods that effectively integrate local wisdom with modern educational technologies. This study explores the potential of Augmented Reality (AR) as a solution to these challenges by developing and implementing AR-based educational media focused on the Megalithic Sites in Poso. The research employed an action research approach, involving a purposive sample of teachers from Poso who participated in a specially designed AR training program. The program included sessions on the relevance of AR to the "Kurikulum Merdeka," hands-on AR application using Assemblr Edu, and strategies for integrating AR into the classroom. The results demonstrate that AR significantly enhances teachers' readiness and confidence in adopting innovative teaching methods, contributing to increased student motivation and understanding of local cultural content. However, challenges such as limited technological infrastructure and the need for continuous teacher training were also identified. The study suggests that with adequate support and training, AR can be a powerful tool in improving educational outcomes in remote areas, fostering a deeper connection between students and their cultural heritage.